Hubungan Status Gizi Ibu Nifas Dengan Produksi ASI - Handayani, Sri; Pratiwi, Yopi Suryatim; Fatmawati, Nurul (Universitas Qamarul Huda Badaruddin, 2018)
Infant mortality is still high in Indonesia, 53% is caused by nutritional factors. Exclusive breastfeeding can reduce infant morbidity and mortality. Breastmilk production is less a complaint that is most often expressed by postpartum mothers and is the cause of exclusive breastfeeding failure. Nutritional status of postpartum mothers has an effect on breast milk production. This study aims to analyze the relationship between nutritional status of postpartum mothers and breast milk production. This research is quantitative research using primary data. The sample in this study were all primiparous mothers in April – May 2017 at Gunung Sari Health Center, who met the inclusion and exclusion criteria. The variables in this study were nutritional status measured from LILA and ASI production as measured by breast milk volume. Analysis using the Mann-Whitney and T unpaired tests. The results showed that there was no relationship between nutritional status and ASI production both seen at day 4 and 10. This is because baby suction is the main factor that influences milk production. Therefore, postpartum mothers are recommended to breastfeed the right way and every two hours in an effort to increase milk production.